Perancangan Gitar Elektrik Terinspirasi dari Album Sob Rock oleh John Mayer - Raden Muhammad Hikman Azka Antono; Maharani Permanasari (Penerbit Itenas, 2024)
This research discusses the design of an electric guitar inspired retro revivalism in John Mayer’s Sob Rock album. The study is aimed to generate an electric guitar design based from visual elements inherent to the Sob Rock album. Double Diamond method is used in this research as a framework to discover and define the visual elements within Sob Rock album, and applies it within the design process to develop and deliver a design solution. In this context, aside from the design’s functionality, creative and aesthethics potentials contained within a popular album are unearthed and thoroughly explored as a basis for an electric guitar design. The outcome of this research is a prototype of an electric guitar design inspired by John Mayer’s Sob Rock album. This product serve not just as a musical instrument, but also as a statement of art within the popular music sphere.